2014
DOI: 10.1186/2047-783x-19-32
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity changes between parietal and prefrontal cortices in primary insomnia patients: evidence from resting-state fMRI

Abstract: BackgroundPrimary insomnia can severely impair daytime function by disrupting attention and working memory and imposes a danger to self and others by increasing the risk of accidents. We speculated that the neurobiological changes impeding working memory in primary insomnia patients would be revealed by resting-state functional MRI (R-fMRI), which estimates the strength of cortical pathways by measuring local and regional correlations in blood oxygen level dependent (BOLD) signs independent of specific task de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
94
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(104 citation statements)
references
References 35 publications
9
94
0
1
Order By: Relevance
“…In the current study, comparison of activated brain regions in the spatial working memory task state between PI patients and controls indicated that activation patterns were consistent with these prior observations. Because the most fundamental characteristic of a spatial working memory is the synergistic effect between the parietal lobe and prefrontal lobe [21] , activation patterns in the bilateral superior parietal lobules and bilateral frontal lobes in the current study notably demonstrated the linkage between such activation and spatial working memory. These findings are concordant with the results of scales score, and weakened activation in the parahippocampal gyrus and bilateral temporal lobes was observed in cases of memory deterioration [21] .…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In the current study, comparison of activated brain regions in the spatial working memory task state between PI patients and controls indicated that activation patterns were consistent with these prior observations. Because the most fundamental characteristic of a spatial working memory is the synergistic effect between the parietal lobe and prefrontal lobe [21] , activation patterns in the bilateral superior parietal lobules and bilateral frontal lobes in the current study notably demonstrated the linkage between such activation and spatial working memory. These findings are concordant with the results of scales score, and weakened activation in the parahippocampal gyrus and bilateral temporal lobes was observed in cases of memory deterioration [21] .…”
Section: Discussionmentioning
confidence: 78%
“…Because the most fundamental characteristic of a spatial working memory is the synergistic effect between the parietal lobe and prefrontal lobe [21] , activation patterns in the bilateral superior parietal lobules and bilateral frontal lobes in the current study notably demonstrated the linkage between such activation and spatial working memory. These findings are concordant with the results of scales score, and weakened activation in the parahippocampal gyrus and bilateral temporal lobes was observed in cases of memory deterioration [21] . Insomnia is a unique and complex physiological process involving interrelationships between varied brain regions, neural networks and neuroendocrine mechanisms.…”
Section: Discussionmentioning
confidence: 78%
“…This abnormal pattern of insula coactivation may indicate that interoceptive awareness of bodily states, one of the established roles of the insula [60,61], is impaired in patients with insomnia. However, the lack of simultaneous EEG recordings to ensure defined states of sleep or wakefulness [56][57][58]62], coupled with application of liberal statistical thresholds, may partially explain variability in findings across resting-state fMRI studies in insomnia.…”
Section: Functional Neuroimagingmentioning
confidence: 96%
“…One study found that individuals with PI had lower functional connectivity within the default mode network in specific areas including the medial prefrontal cortex with the right medial temporal lobe and the left medial temporal lobe with the left inferior parietal cortices [75]. Another study that used the superior parietal lobule (a major node of both executive control and default mode networks) as the seed region found that patients with PI, compared to GS, had higher connectivity of this region with the anterior cingulate, left posterior cingulate, right inferior frontal gyrus, right insula, and precuneus [76]. These are all regions of the brain involved in conscious awareness.…”
Section: Functional Neuroimaging Studies Of Insomniamentioning
confidence: 99%